Directors' liability during corporate insolvency; The legal framework, relevance and efficacy of the wrongful trading rule in Malawi - Boraine, A. (Andre), 1957- (University of Pretoria, 2022)
Thesis (LLD (Mercantile Law))--University of Pretoria, 2022.